ปัจจัยที่ส่งผลต่อคะแนนพัฒนาการวิชาคณิตศาสตร์ของนักเรียนชั้นมัธยมศึกษาปีที่ 3 - ศุภลักษณ์ ใจแสวงทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this research were 1) to study factors effecting the growth scores in mathematics 2) to test the model invariance between male and female students and 3) to test the model invariance between dichotomous growth scores and partial credit growth scores. The developed model consisted of 7 latent variables and 12 observed variables. The research samples consisted of 334 mathayom suksa three students and 11 teachers under the Department of General Education, Bangkok Metropolis. The data of growth scores in mathematics were secondary data obtaining from repeated measures, three-time-point measurement of mathematics achievement, with a four-week time-lag and using the same tests. Data were analyzed by descriptive statistics, Pearson’s product moment correlation and advance statistical with path analysis and multi-group analysis by LISREL. The major findings were as follows: 1. The model of growth scores in mathematics of mathayom suksa Three students was valid and fit to the empirical data. The model indicated that the Chi-square goodness of fit test was 2.295, df = 5, p = 0.807, GFI = 0.999, AGFI = 0.982 and RMR = 0.017. The model accounted 58.9 % of variance in growth scores of mathematics. 2. The growth scores in mathematics received the highest direct effects from economic of parents. The next direct effects were prior achievement, education of teacher and attitude toward mathematics of student. The growth scores in mathematics received the highest indirect effects from education of parents which pass on economic of parents and attitude toward mathematics. The next indirect effects were economic of parents which pass on prior achievement and education of teacher which pass on attitude toward mathematics. 3. The model of growth scores in mathematics of male and female students in mathayom suksa Three students indicated invariance of model form and parameter LX LY and GA. 4. The model of growth scores in mathematics of Mathayom Suksa Three students from dichotomous growth scores and partial credit growth scores indicated invariance of model form and parameter LX LY GA BE and PS.